On the cost-effectiveness of national economy-wide greenhouse gas emissions abatement measures. (May 2019) - Sotiriou, Chryso; Michopoulos, Apostolos; Zachariadis, Theodoros
Abstract: This paper explores cost-effective greenhouse gas abatement options for the European Union Member State of Cyprus, for those sectors of the national economy that are not subject to the European Emissions Trading System. The analysis leads to the construction of a baseline and several alternative marginal emission abatement cost curves. It addresses all economic sectors and considers all different types of mitigation measures – improving energy efficiency, switching to low- or zero-carbon fuels, and inducing behavioural change towards public transport modes. We apply nationally appropriate data that are mainly derived from local market information and judgement of national experts. Finally, we present results of several sensitivity analyses, which address main shortcomings of marginal abatement cost curves that have been identified in the literature, and discuss the policy implications of each one of them. Apart from its relevance for EU Member States, this assessment is useful for all countries seeking guidance in their decarbonisation strategies. Highlights: We explore cost-effective greenhouse gas abatement options for Cyprus. All types of measures considered: energy efficiency, fuel switch, behavioural change. Construction of baseline and alternative marginal emission abatement cost curves. Sensitivity analyses address shortcomings of such cost curves. Assessment is useful for any country seeking guidance in decarbonisation strategy.